STRUCTURE OF THE CRITICALY ILL PATIENTS IN INTENSIVE CARE UNIT IN CARIL:ANALYSIS FOR YEAR 2011 - Arsovska A; Nikolova-Todorova Z; Arsovski O; Jovanovski-Srceva M (SHMSHM/AAMD, 2012)
ritically ill patients are in veryfragile pathophysiological con- dition in which only small changes can lead to vital organ dysfunction. Re- serves of the organism among these patients are decreased and they need complex and dynamic intensive therapy and continuous monitoring of vital parameters. Intensive care units are specially designed and equipped with appropriate technical devices and special trained medical team for treatment of critically ill patients. Objective: The aim of this study was to evaluate the structure of the patients who were treated in the Intensive Care Unit (ICU) of the Clinic of Anesthesia, Reanimation and Intensive care during 2011, in- dication for admission in ICU (trauma, postoperative treatment or nonsur- gical illness), duration of treatment in ICU and indication and duration of mechanical ventilation. Patients and methods: This retrospective study in- cludes patients who had been treated in ICU in CARIL during 2011. Method of statistical analysis were processed following parameters: age, gender, reason for the admission to the ICU (trauma, postoperative treatment or non-surgical disease), duration of the medical treatment in ICU (total and selected), duration of the mechanical ventilation depending on the ad- mission criteria. Results: During year 2011 in ICU in CARIL 981 patients were treated, from which most of the patients had postoperative medical treatment 523 (53.31%), other were non-surgical patients 267 (27.22%) and trauma patients 191 (19.47%). Mechanical ventilation was indicated in 645 patients (65.76). Conclusions: Mean age of the patients was 59 ±27 years, 66.6% were male, 53% were patients who were admited in ICU due to post- operative treatment. Mean value of the duration of the medical treatment in ICU was 12 days.65.7% of patients needed mechanical ventilation, a average number of days on mechanical ventilation was 10 days. The total mortality was 24%.
Keywords: Intensive medical treatment; addition in ICU; demographic characteristics